Interfacial Water Drives Improved Proton Transport in Siliceous Nanocomposite Nafion Thin Films. Issue 4 (22nd September 2017) - Goossens, Pieter‐Jan; Vallaey, Brecht; Verlinden, Jesse; Martens, Johan A.; Rongé, Jan
Abstract: Nafion proton exchange membranes dehydrate when they are used in the gas phase and in high‐temperature applications, such as fuel cells and (photo)electrolysis. Retaining a high level of membrane hydration under such conditions can be achieved by using inorganic fillers, but has never been demonstrated for thin films. Herein, several types of siliceous nanoparticles were incorporated for the first time into Nafion thin films. For composite Nafion materials, increased water uptake does not always induce increased proton conductivity. Here, increased water uptake did result in higher proton conductivity due to a synergistic effect within the composite film. The nanocomposites displayed a higher water uptake than could be expected based on the water uptake of the individual materials. Excess water present at the Nafion–filler interface was found to cause the proton conductivity of nanocomposite Nafion/Ludox AS‐40 thin films to double compared with pristine Nafion at low relative humidity (from 2 to 4 mS cm −2 ). Knowledge about the properties of such interfaces will allow for the better design of self‐humidifying nanocomposite Nafion membranes, films, and catalyst layers. Abstract : Better wetting : Enhanced proton conduction in nanocomposite Nafion thin films is caused by excess water located at the Nafion–silica filler interfaces (see picture). The introduction of foreign materials to induce structures has not been investigated previously, but is shown to be a promising avenue for applications in air‐based photoelectrochemical cells.